Kajian Kesalahan Berbahasa dalam Teks Berita Siswa SMA Negeri 2 Kuningan : Dampak Terhadap Pemahaman dan Penyampaian Informasi - Naura Inaya Zalfa; Azmi Naufa Hawari; Rossiani Aulianti; Ai Siti Nurjamilah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Submitting information in the form of news texts has an important role in mass communication, including in the educational context. One type of text that is often used in schools is news text, which aims to improve students' writing and reading skills. However, many language errors are found in news texts written by students, both in the use of spelling, punctuation, sentence structure, and arrangement of ideas, which can reduce reader understanding and the effectiveness of conveying information. This research aims to identify types of language errors in news texts written by SMA Negeri 2 Kuningan students, as well as analyzing their impact on understanding and conveying information. The method used is descriptive qualitative with a language error analysis approach in news texts regarding Mount Ibu activities. The results showed that the most frequently found errors included aspects of morphology, syntax, semantics and phonology. These errors, even though they seem trivial, can affect the clarity of the message conveyed in the news text. Based on these findings, it is recommended that there be improvements in the use of punctuation, choosing more appropriate words, as well as training for students in writing news texts to make them more effective and easier to understand. It is hoped that this research can contribute to improving the quality of news writing in schools, especially in Indonesian language learning.